O sistema imune dos insetos e o controle de algumas doenças parasitárias humanas - Menezes, Hércules [UNESP]; Álvarez Mosig, José M. (My University, 1999)
Parasitic diseases in humans, transmitted by insects, affect about 500 million people living mainly in countries of low economic power. The control of these diseases is difficult to carry out, mianly due to social and political problems, enhanced by the capacity of these organisms to develop resistance to insecticides used to for their destruction. Some recent advances in the area of insect immunology have open the possibility for abetter epidemiological control of these diseases. The immune system of these insects, as well as that of other organisms, have the ability to recognize the infecting parasites and liberate a series of reactions which stop the infection. These reactions involve the circulating cells (hemocytes) against the parasite. These cells have the ability of phagocytize and liberate the production of various humoral factors, neutralizing the infection. Some promising results, obtained by the study of the immune system of malaria-transmitting insects, the sleeping disease, and dengue, are an example of this new sanitary strategy.